Psychosocial Factors Related to Lateral and Medial Epicondylitis: Results from Pooled Study Analyses - Thiese, Matthew S. (J Occup Environ Med, 2016)
OBJECTIVE: The goal is to assess the relationships between psychosocial factors and both medial and lateral epicondylitis after adjustment for personal and job physical exposures. METHODS: 1824 participants were included in pooled analyses. 10 psychosocial factors were assessed. RESULTS: 121 (6.6%) and 34 (1.9%) participants have lateral and medial epicondylitis respectively. Nine psychosocial factors assessed had significant trends or associations with lateral epicondylitis, the largest of which was between physical exhaustion after work and lateral epicondylitis with and odds ratio of 7.04 (95% CI=2.02-24.51). Eight psychosocial factors had significant trends or relationships with medial epicondylitis, with the largest being between mental exhaustion after work with an odds ratio of 6.51 (95% CI=1.57-27.04). CONCLUSION: The breadth and strength of these associations after adjustment for confounding factors demonstrate meaningful relationships that need to be further investigated in prospective analyses.